The anatomy of prejudices - Young-Bruehl, Elisabeth 1946-2011 (Harvard Univ. Press, 1996)
Surveying the study of prejudice since World War II, Young-Bruehl finds a history riddled with assumptions, generalizations, and cliches. The Anatomy of Prejudices proposes a fresh start, and suggests an approach that distinguishes between different types of prejudices, the people who hold them, the social and political settings that promote them, and the human needs they fulfill. Young-Bruehl draws on theoretical and clinical, historical, and empirical literatures to show us prejudices from a variety of angles: there are those that help protect a group's identity (ethnocentrisms) and those that project a group identity (ideologies of desire); there are prejudices as socioeconomic phenomena, attitudes toward governments, products of historical periods, social mechanisms of defense, sexual fantasy structures, and puberty rites